Dynamic hip screw technique in the management of trochanteric fracture - Rao, N. V. Narasimha; Krishna, C. Siva Rama; Aditya, K.; Chandra, T. Jaya (International Journal of Research in Orthopaedics, 2019)
Background: Study was conducted to find the results of dynamic hip screw in the management of trochanteric fracture by analyzing the factors which influence post-operative mobility. Methods: Study was conducted in the department of orthopedics, GSL Medical College. Individuals >18 years, both genders who were diagnosed having trochanteric type I and II Boyd and Griffin stable fractures were included in the study. All surgeries were performed under spinal anesthesia, internal fixation with dynamic hip screw and 135o angled blade plate. Injectable third generation cephalosporins were used 24 hours preoperatively, intra- operatively and 5 days post-operatively, and oral antibiotics till suture removal. Patients allowed to sit on bed on 2nd and 3rd day and static quadriceps exercises were started from 2nd day onwards, hip and knee flexion exercises from 6 or 7th day and weight bearing walking form 10th day. Results: The average age was of the participants was 61.53 years, ranged between 41 to 80 years; 65% were female participants and 35% were male patients. In the study, 20 (50%) patients had right side fracture and left sided affection of trochanteric fracture to the remaining 50%. Most of the patients (67.5%) in this study were classified as type II Boyd and Griffin criteria, and 32.5% were type I. The clinical and functional outcome was calculated using the Kyle's criteria; 25% (10) showed excellent response, followed by good (50%), fair (15%) and poor (10%) results. Conclusions: Dynamic hip screw is the operative treatment of choice for stable trochanteric fractures. However, studies on large sample for long time are recommended.